Stella Aurorae: Natal University College Volume 2 Natal University College: Natal University College (1949 to 1976) - Guest, Bill; Guest, Bill (Natal Society Foundation, 2017)
This is the second of a three-volume history by Bill Guest of a major South African university founded as the Natal University College in Pietermaritzburg in 1909. Despite trying conditions, including two world wars, the university expanded, developed a second campus (Howard College) in Durban and became the University of Natal in 1949.The first volume covered the history of Natal University College from 1909 to 1949. This volume covers the years 1949 to 1976 during which the university continued to develop as a dual-centred institution while struggling to maintain its autonomy. This included control of a new third campus, a blacks-only medical school, in the face of interference from the apartheid government. The administrative centre of gravity shifted inexorably towards Durban as student enrolments and course options increased in the larger city. In addition to other sources the author draws extensively on the university archives of publications, reports, documents, reminiscences and minutes of meetings, recalling both the serious as well as the lighter side of campus life.